70 Years of Popeye - Fleischer, Dave; Sparber, Isidore; Kneitel, Seymour; Tendlar, David (Winstar, 2000)
Everyone's favorite squinty-eyed, spinach-chompin' sailor is back in this collection of 12 animated classics, which are quite humorous and, in typical Popeye fashion, strong to the finish. The cartoons have been digitally restored with enhanced picture and sound, and feature new sound effects delightfully mixed with original dialogue. The color and texture are as bright and as clear as they would have been at their original theatrical release. All the familiar characters - Bluto, Olive Oyl, Wimpy - make appearances and prove that certain antics never fail to entertain, even decades after their introduction. [www.amazon.com]